Theories on Law and Ageing The Jurisprudence of Elder Law - Doron, Israel. (Springer Berlin Heidelberg, 2009)
The fundamental idea of "law and aging" as a discrete category of legal principle and theory is controversial: What special feature and characteristics of "older adults" justify and even require a particular theoretical approach? Is it possible to formulate legitimate generalizations about a group identified as "older adults", while avoiding the harmful stereotypes of ageism? And what if anything is gained by the approach? In an attempt to provide answers to these difficult questions, this book presents a collection of different theoretical frameworks to the field of law and ageing. Written by the leading scholars in the field, this book describes the diverse and rich theoretical landscape of this field, and argues that time has come to recognize the importance of "Jurisprudential Gerontology" for the future development of the socio-legal science of ageing.